Report of deputation to Minister of Health on "A National Health Service"...
1945-03 1945 1940s 8 pages -6- Nursing and Ambulance Services The obligations in regard to the nursing service were very wide and it was hoped and intended that great progress should be made and that representatives of nurses would be on the advisory bodies set up. There was a great deal to be done so far as ambulance services were concerned and much had been learnt during the war. They should not be tied to local authority boundaries but should be organised on a narrower basis than the nation as a whole - the areas could take a real pride in organising the ambulance service. Industrial Medicine From Mr. Allen's statement it appeared that the T.U.C. approach had much in common with that of the medical profession. They regretted the division between industrial medicine and the care of personal health. The Government had set out the view on page 10 of the White Paper that just as a school medical service was needed, so the Minister of Labour had a special medical need in the sphere of his work. That service could not be integrated at the moment all under one service or organisation but it was true that in various ways there had been growing up during the war both in Government organisations and in privately owned factories a development of medical officers and works doctors. One thing that should be ensured was that there should be a closer co-ordination at the centre as between those medical services but in the time within which the health statute had got to become law it was not possible to deal with that complete integration of health services. The Health Service had to be related to the rest of the Social Insurance Scheme and it was therefore not wise to tackle too much if the whole of the undertaking was to come in within a reasonable time. Mr. Johnstone in referring to Mr. Allen's statement that there should be no contracting out of the scheme said that if he meant that there should be absolute prohibition of any contracting out from payment by legal obligation from everybody to the State Service, he could have the fullest assurance on that point. It was going to be a 100 per cent. scheme but once a man had paid into the scheme, if he chose to opt to pay somewhere else for a little while, that could not be prevented at the moment. Rehabilitation Everyone in the Government he was sure agreed that rehabilitation was vital. During the war rehabilitation had made great strides in experimentation which no Government could ever depart from in post-war years. The finest luxury hotels in Scotland were taken over for rehabilitation purposes at the present time, particularly the one at Gleneagles for the rehabilitation of injured miners and it was an amazing spectacle to see men with broken backs getting cured and restored to industry instead of as previously sitting round a fireside ekeing out a miserable existence on disablement pay and then dying off. Works Doctors They had not been able to link up the question of the works doctor entirely in the Government proposals for reasons of which he was sure the deputation were well aware. To some extent they were being linked up even at the present time. In the Emergency Hospital for example recommendations from works doctors 292/847/3/118